High somatostatin receptor expression and efficacy of somatostatin analogues in patients with metastatic Merkel cell carcinoma. (16th June 2020) - Akaike, T.; Qazi, J.; Anderson, A.; Behnia, F.S.; Shinohara, M.M.; Akaike, G.; Hippe, D.S.; Thomas, H.; Takagishi, S.R.; Lachance, K.; Park, S.Y.; Tarabadkar, E.S.; et al.
Summary: Background: Merkel cell carcinoma (MCC) is an aggressive, high‐grade, cutaneous neuroendocrine tumour (NET). Agents blocking programmed death 1/programmed death ligand 1 have efficacy in metastatic MCC (mMCC), but half of patients do not derive durable benefit. Somatostatin analogues (SSAs) are commonly used to treat low‐ and moderate‐grade NETs that express somatostatin receptors (SSTRs). Objectives: To assess SSTR expression and the efficacy of SSAs in mMCC, a high‐grade NET. Methods In this retrospective study of 40 patients with mMCC, SSTR expression was assessed radiologically by somatostatin receptor scintigraphy (SRS; n = 39) and/or immunohistochemically when feasible ( n = 9). Nineteen patients (18 had SRS uptake in MCC tumours) were treated with SSA. Disease control was defined as progression‐free survival (PFS) of ≥ 120 days after initiation of SSA. Results: Thirty‐three of 39 patients (85%) had some degree (low 52%, moderate 23%, high 10%) of SRS uptake. Of 19 patients treated with SSA, seven had a response‐evaluable target lesion; three of these seven patients (43%) experienced disease control, with a median PFS of 237 days (range 152–358). Twelve of 19 patients did not have a response‐evaluable lesion due to antecedent radiation; five of these 12 (42%) experienced disease control (median PFS of 429 days, range 143–1757). The degree of SSTR expression (determined by SRS and/or immunohistochemistry) did not correlate significantly with the efficacy endpoints. Conclusions: In contrast to other high‐grade NETs, mMCC tumours appear frequently to express SSTRs. SSAs can lead to clinically meaningful disease control with minimal side‐effects. Targeting of SSTRs using SSA or other novel approaches should be explored further for mMCC. Abstract : What is already known about this topic? Merkel cell carcinoma (MCC) is an aggressive, high‐grade neuroendocrine tumour (NET) of the skin. Blockade of programmed death 1/programmed death ligand 1 is associated with high response rates in metastatic MCC, but approximately half of patients do not respond and need alternative therapeutic options. Somatostatin analogues (SSAs) are frequently used for treatment in low‐ and medium‐grade NETs but are typically not considered for high‐grade NETs due to presumably low expression of somatostatin receptors (SSTRs). What does this study add? A high proportion (85%) of metastatic MCC tumours express SSTR by somatostatin receptor scintigraphy (SRS), in striking contrast to other high‐grade NETs. SSAs can lead to clinically meaningful disease control with minimal side‐effects in some patients with metastatic MCC who are not candidates for or did not benefit from immunotherapy. What are the clinical implications of this work? The high frequency of SSTR expression by SRS in metastatic MCC, a high‐grade NET, offers a strong rationale for therapeutic SSTR targeting, using either SSAs or other emerging approaches. SSTR targeting may be especially relevant for those patients with metastatic MCC who are not eligible for or do not respond to immunotherapy. Linked Comment: Samimi and Becker. Br J Dermatol 2021; 184:195–197 . Plain language summary available online